Inovasi Bimbingan Kelompok Berbasis Film: Studi Eksperimen Cinematherapy dalam Konteks Perencanaan Karier Siswa - Pravesti, Cindy Asli; Sugiri, Danang Joyo; Mukhoiyaroh, Mukhoiyaroh; Maghfira, Ervinda Rosana; Mufidah, Elia Firda; Lathifah, Maghfirotul (Universitas Muria Kudus, 2025)
This study aims to examine the effectiveness of using cinematherapy in group counseling services to improve career planning among 11th-grade students at SMA Dharma Wanita 4 Taman. The background of the research is the students' lack of self-awareness and clear career goals, as well as the limited impact of conventional counseling services in addressing affective and reflective aspects. The study employed a pre-experimental one-group pre-test post-test design with a purposive sample of four students. The treatment was delivered through five group counseling sessions utilizing educational films with career-related messages, such as Monster University and Kung Fu Panda 3. The instrument used was a career planning scale based on three aspects: self-knowledge, attitude, and skills. Data analysis using the Wilcoxon Signed-Rank Test showed an increase in scores, although the results were not statistically significant (p = 0.125). Nevertheless, practical improvements were observed in the participants’ self-understanding and career direction. These findings suggest that cinematherapy holds promise as an innovative approach in school-based career guidance services, especially in fostering emotional reflection, enhancing self-efficacy, and strengthening students’ career orientation